229k views
1 vote
Find h(-3), h(O), and h(4) for the following function.

h(x) = 9x2 - 3
h(-3) =
(Simplify your answer.)
h(O) = (Simplify your answer.)
h(4) = (Simplify your answer.)

Find h(-3), h(O), and h(4) for the following function. h(x) = 9x2 - 3 h(-3) = (Simplify-example-1
User Claudio
by
4.8k points

1 Answer

2 votes

Answer:

h(-3) = 78

h(0) = -3

h(4) = 141

Explanation:

We have to find the numeric values for the function at
x = -3, x = 0 and
x = 4. We find this replacing x by this values. So

x = -3


h(-3) = 9*(-3)^2 - 3 = 81 - 3 = 78

So

h(-3) = 78

x = 0


h(0) = 9*(0)^2 - 3 = 0 - 3 = -3

So

h(0) = -3

x = 4


h(4) = 9*(4)^2 - 3 = 144 - 3 = 141

So

h(4) = 141

User Aryeh Beitz
by
4.7k points